The Role of Human Resource Management and Business Administration in Enhancing Tourism and Regional Development: An Empirical Study in Banten Province - Basrowi Basrowi; Fauzi Fauzi; Rustam Efendi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the role of human resource management (HRM) and business administration in enhancing tourism development and promoting regional growth in Banten Province, Indonesia. The research is driven by the increasing contribution of tourism to local economic development and the strategic importance of HRM and administrative practices in improving service quality, organizational efficiency, and sustainable competitiveness. A quantitative approach was employed, involving a population of 5,000 business and tourism-related workers, with a proportional random sample of 150 respondents. Data were collected using structured questionnaires and analyzed through structural equation modeling (SEM) to investigate the relationships among HRM practices, business administration effectiveness, and tourism development outcomes. The results reveal that HRM practices significantly enhance administrative performance and service quality, which in turn positively influence tourism performance. The findings underscore that effective HRM strategies—including training, motivation, and performance evaluation—are crucial in strengthening business administration and advancing tourism competitiveness. This study contributes to the understanding of HRM and business administration in the tourism sector and provides practical insights for policymakers, business leaders, and tourism stakeholders aiming to foster sustainable regional development.